2014
DOI: 10.1007/s00392-014-0718-y
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular sequelae of radiation therapy

Abstract: Radiotherapy (RT) is one of the main therapeutic options for malignancy treatment; nevertheless, RT is not free from side effects, including an increased risk for secondary neoplasms and other organs injury. Cardiovascular complications are the second most frequent fatal post-RT sequelae, which physicians should be aware of and ready to diagnose early and cure. This review therefore aims to examine epidemiology, pathogenesis and clinical dose-correlated manifestations of RT-induced cardiovascular disease. Futu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 115 publications
1
14
0
2
Order By: Relevance
“…10 However, some recent review articles still seem to mostly underline the importance of radiation dose, largely omitting the effect of beam energy. 11,29 In our study, there was a trend of increased risk of malfunctions in ICDs compared to PMs, which goes in line with previous reports that ICDs might be more sensitive to ionizing radiation than PMs. 13,30 Unexpectedly, we observed that device malfunctions were associated with location of the RT fields below the diaphragm.…”
Section: Predictors Of Device Malfunctionssupporting
confidence: 92%
See 1 more Smart Citation
“…10 However, some recent review articles still seem to mostly underline the importance of radiation dose, largely omitting the effect of beam energy. 11,29 In our study, there was a trend of increased risk of malfunctions in ICDs compared to PMs, which goes in line with previous reports that ICDs might be more sensitive to ionizing radiation than PMs. 13,30 Unexpectedly, we observed that device malfunctions were associated with location of the RT fields below the diaphragm.…”
Section: Predictors Of Device Malfunctionssupporting
confidence: 92%
“…The risks associated with photon beam energy are also acknowledged in the recently published Dutch guidelines, in which patients undergoing RT with >10 MV photons are considered at high risk of device malfunction regardless of the dose to the PM/ICD . However, some recent review articles still seem to mostly underline the importance of radiation dose, largely omitting the effect of beam energy …”
Section: Discussionmentioning
confidence: 99%
“…1d-e-f). One-year follow-up was uneventful.RT is a well-recognized risk factor for cardiovascular disease, ranging from pericarditis and arrhythmias to silent ischemia and vasculopathy [4]. To the best of our knowledge, we are reporting one of the first cases of isolated aortic plaque on the descending thoracic aorta probably associated to breast RT.…”
mentioning
confidence: 89%
“…Ionizing radiation is known to affect the cardiovascular system detrimentally in radiotherapy patients [24, 25]. Recent analyses point to an effect of radiation already for low and medium doses [2629] but the main biological mechanisms are unknown.…”
Section: Introductionmentioning
confidence: 99%